An Experimental Study: Multimedia Reading Materials on Teaching Reading Comprehension - s. siswandi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
The main focus of this research is to investigate whether there was a significant effect of using Multimedia Reading Materials on students’ reading comprehension of narrative text at SMA Negeri 12 Pekanbaru. This research had two variables, Multimedia Reading Materials as an independent variable and students’ reading comprehension as a dependent variable. This research was a quasi-experimental research. The writer selected two classes from total eleven classes by using cluster random sampling technique: experimental and control class. There were 70 students as sample out of 391 students. In collecting the data, the writer used multiple choice and short-answer question test. In analyzing the data, the writer used independent sample t-test formula calculated by using SPSS 25 version continued by using eta-square formula. Based on the analysis of t-test Formula, the sig. value is 0.000. It could be stated that 0.000<0.05. Then, the effect size is 0.41 categorized into moderate level. The writer concluded that there is significant effect of using Multimedia Reading Materials on students’ reading comprehension of narrative text at SMA Negeri 12 Pekanbaru. And the biggest effect was occurred on the fourth component of reading comprehension that is identifying the meaning of words where the effect size is 0.14 categorized into large effect.